2021
DOI: 10.3390/su13105527
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Business Schools’ Pedagogy on Sustainable Business Practices and Ethical Decision-Making

Abstract: Business school curriculums are designed to improve business skills and a student’s eventual workplace performance. In addition to these business skill sets the emerging business environment demands softer skills associated with ethical decision-making and sustainable business practices. The objective of the study is to identify the key influencers of ethical orientation and attitudes towards the environment as a first critical step for curriculum planning designed to develop both ethical decision-making and e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 92 publications
(129 reference statements)
0
4
0
1
Order By: Relevance
“…Close to 49% of participants were recruited from a course with a sustainability focus. With the exception of the high number of females (38% versus 65%), the sample was representative of the target population at Lang [56]. All undergraduate participants were registered in one of 11 subprograms housed within the Bachelor of Commerce program.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Close to 49% of participants were recruited from a course with a sustainability focus. With the exception of the high number of females (38% versus 65%), the sample was representative of the target population at Lang [56]. All undergraduate participants were registered in one of 11 subprograms housed within the Bachelor of Commerce program.…”
Section: Resultsmentioning
confidence: 99%
“…The PIR scale is a promising scale for selection by schools like the Lang School of Business who 'are committed to using business as a force for good to achieve the United Nation's SDGs' [56]. In addition to providing a benchmark for a business school's performance as perceived by students, arguably its most important stakeholder, it is a tool that could help 'attract students and faculty who have a social conscience, an environmental sensibility, and a commitment to community involvement' [56]. Building an organizational culture that is aligned with the mission, vision, and core values of the institution is critical to achieving an organization's intended goals.…”
Section: Discussionmentioning
confidence: 99%
“…The following section shares references that partly represent the state of the art in relation to the central focus of the article. For example, the study conducted by Rodenburg and Macdonald (2021), proposed the identification of influential factors that would be key to ethical orientation and attitudes towards the environment for curricular planning designed to Ethics of care in environmental ethics develop both ethical decision making and environmental sensitivity of students in business schools. The results showed that in addition to sociocultural variables, situational factors also influence ethical decision making.…”
Section: Related Previous Studiesmentioning
confidence: 99%
“…The level of sustainable development is also influenced by the skills of the management and employees, their knowledge, flexibility, and the ability to adapt to the changing market environment. Therefore, the level of education in society, self-employment, or the development of students and their international mobility also contribute to a new perception of socioeconomic reality and greater activity in the fight against climate change (Hind et al, 2009;Abdelkafi and Täuscher, 2016;Rodenburg and MacDonald, 2021).…”
Section: Conceptual Backgroundmentioning
confidence: 99%